USA Diving coach development reference manual - Malina, R. M.; Mathews, M. E.; Anderson, S. J. (USA Diving Publications, 2006)
The newly published USA Diving Coach Development Manual is a must-read for all coaches. The book features 783 pages and 50 chapters on a variety of areas important to coaches of all levels of divers. Featured topics include Growth, Development and Learning; Training, Conditioning and Nutrition; Social/Psychological Aspects of Coaching; Technical Diving Skills, Progressions and Analysis; Teaching and Coaching; and Professional Preparation and Development. A history of diving is also included.